Demonstration of automatic gearbox II / Mahadi Draman - Draman, Mahadi (2001)
Chapter 1 describes the details of automatic gearbox. The most important part in the automatic transmission, the epicyclic gear train is highlighted. Chapter 2 describes about planetary gear set. The importance of this chapter is that the working of the planetary gear train under different gears are explained. Chapter 3 describes about the operation of automatic transmission especially the project model F3A21 from Proton Wira. This model is different from the other automatic transmission used in automobiles. Chapter 4 describes how the power is transmitted from input to the output under different gear conditions. For more details we showed the fluid diagram to indicate the working principle of this gear box. Chapter 5 is the conclusion of this final project and the suggestions for improving this project work in future.